A Series of Metal‐Organic Frameworks for Adsorption of Halogenated Volatile Organic Compounds. Issue 45 (5th December 2022) - Nguyen, Phuong T. K.; Tran, Y B. N.
Abstract: Given the urgent demand for removing toxic vapours from the atmosphere, the employment of porous materials for the adsorption of halogenated volatile organic compounds has been of intense interest. In this respect, a series of isostructural metal‐organic frameworks (MOFs), M‐MOF‐184 (M=Mg, Co, Ni, Zn), was solvothermal synthesized and examined on adsorption of 1, 2‐dichloroethane. Due to the structural features of Lewis acidic sites derived from the infinite metal‐oxo unit and basic sites from 2‐oxidobenzoate anions, accessibly hexagonal channels with an aperture size of 24 Å, and high porosities (BET surface areas>3000 m 2  g −1 ), three M‐MOF‐184 (M=Mg, Co, Ni) materials revealed the high saturated capacity of 1, 2‐dichloroethane at room temperature (> 236 cm 3 g −1 ). Notably, the adsorption capacities of three M‐MOF‐184 (M=Mg, Co, Ni) frameworks for 1, 2‐dichloroethane outperformed that of the porous materials including activated carbon and representative MOFs. Among this series, Co‐MOF‐184 showed the largest adsorption saturated capacity of 1, 2‐dichloroethane (346 cm 3  g −1 at 298 K) and highly isosteric heat of adsorption (40 kJ mol −1 ). By mean of ATR‐FTIR analysis, we determined the surface interactions between 1, 2‐dichloroethane and the Co‐MOF‐184 and explore the important effects of the acidity and basicity properties and large pore structure on 1, 2‐dichloroethane adsorption performance. Abstract : A new series of isostructural metal‐organic frameworks (MOFs), termed M‐MOF‐184 (M=Mg, Co, Ni, Zn), was synthesized for the adsorption of 1, 2‐dichloroethane vapour. Due to the synergetic features of the strongest basicity of 2‐oxidobenzoate anions, lowest acidity of Co sites, high surface area, and large pore aperture, Co‐MOF‐184 revealed an outstanding saturated capacity of 1, 2‐dichloroethane at 298 K.